Diquafosol sodium reduces neuronal activity in trigeminal subnucleus caudalis in a rat model of chronic dry eye disease. (1st January 2023) - Katagiri, Ayano; Tsubota, Kazuo; Mikuzuki, Lou; Nakamura, Shigeru; Toyofuku, Akira; Kato, Takafumi; Bereiter, David A; Iwata, Koichi
Highlights: Diquafosol sodium, P2Y2 receptor agonist, increased tear volume in chronic dry eye. Diquafosol sodium attenuates ocular pain in chronic dry eye. Diquafosol sodium suppresses phosphorylation of ERK in the Vc of chronic dry eye. Diquafosol sodium attenuates neuronal activity in the Vc of chronic dry eye. Abstract: Patients with persistent and severe dry eye disease (DED) have corneal hypersensitivity, resulting in ocular pain, and diquafosol sodium, a potent P2Y2 receptor agonist, is commonly used to improve the resultant tear film stability. This study determined the effects of diquafosol instillation on the suppression of trigeminal subnucleus caudalis (Vc) neuronal activity and ocular pain by enhancing tear film stability in the model for chronic DED. The effects of diquafosol on the ocular surface were assessed by the topical application for 28 days, starting from the 14th day since unilateral exorbital gland removal (chronic DED). Loss of tear volume secretion in chronic DED rats was significantly reversed by diquafosol instillation after 28 days, compared with saline treatment. The number of eyeblinks and pERK-IR neurons in the superficial laminae of Vc following hypertonic saline administration to the ocular surface was lower in diquafosol-treated chronic DED rats than in saline-treated rats. The neuronal activity evoked by hypertonic saline and mechanical stimulation along with the spontaneous neuronal activity in the superficial laminae of the Vc were suppressed in diquafosol-treated chronic DED rats. These findings suggest that ocular surface instillation of diquafosol for 28 days attenuates the neuronal hyperactivity in the Vc and the ocular pain that often occurs in chronic DED.